Contribution factors to transformer failure under no load condition and mitigation action - Ismail, Daut; Shahanom, Uthman; Young Zaidey; Dina Maizana, Maiz Ahmad; Moses, Anthony J. (Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 2008)
Organized by Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 19th - 20th December 2006 at Batu Pahat, Johor.